Entrepreneurial Potential of Young People and Future Experts Training in the Field of Technological Entrepreneurship in University Environment: An Empirical Study - Anna N. ZAKHAROVA; Tamara V. TALANOVA; Nina G. GUBANOVA; Anna N. ERLYGINA; Anna S. GROMOVA; Alena Yu. NIKOLAEVA (Communications of International Proceedings, 2023)
The development of youth entrepreneurship is beneficial for society and the economy. Planning for the development of youth entrepreneurship includes the promotion of entrepreneurial culture, the introduction of educational studies at the level of schools and universities, providing mentoring when starting a business, etc. Research on the development of student entrepreneurship in educational institutions is analyzed in the article. The results of an empirical study of the characteristics of emotional intelligence, professional personality type are covered in the article. The results of the research will find their application in the work of acceleration programs to support project teams and student initiatives for the formation of innovative products, training programs of entrepreneurial competencies for students in educational institutions of higher education in the conditions of the regional Russian educational space.
Keywords: student technological entrepreneurship; youth technological entrepreneurship; team roles; emotional intellect.